Konsep Ekonomi Islam pada Masa Bani Umayyah, Bani Abbasiyah, dan Turki Usmani - Ahmad Ruyat Ismail; Zainal Arif (Journal on Education, 2025)
This paper discusses the concept of Islamic economics as applied during three caliphate periods: the Umayyad Caliphate, the Abbasid Caliphate, and the Ottoman Empire. Each of these periods played a significant role in introducing and developing economic principles based on Sharia law, encompassing areas such as taxation systems, land management, trade, and banking, as well as endowments (waqf). We hope this paper provides deeper insights into how Islamic economics has been implemented since the time of the caliphates and the important contributions it has made to the history of Islamic civilization. Islamic economics is an economic system derived from Islamic values, guided by the Quran, Hadith, and the ijtihad (independent reasoning) of Islamic scholars. This concept aims to achieve human welfare through justice, honesty, and prosperity without exploitation or oppression. During the Islamic caliphate periods, such as the Umayyad, Abbasid, and Ottoman eras, Islamic economic principles were applied in various fields, including banking, trade, and state administration. This paper explores the development of Islamic economics during each of these periods and their respective contributions to building the Islamic economic system.